The study of mass loss intensity of plum fruits during storage - Сердюк, Марина Єгорівна; Степаненко, Дмитро Сергійович; Кюрчев, Сергій Володимирович (Eastern-European Journal of Enterprise Technologies, 2016)
The study deals with scientific substantiation of the influence of the main chemical composition constituents and stressful weather factors of the growing season on the natural mass loss intensity of plum fruits during storage and development of a mathematical model for predicting this process. The fruits of plum varieties Voloshka, Stanley and Uhorka Italiis'ka were objects of the study. The fruits were stored at 0... –1 °C, relative humidity of 90±1 %. The study revealed that weather in the years under research was highly changeable and had many stressful factors. The highest dry matter content, including sugars and organic acids, was present in the fruits of plum variety Voloshka, higher ascorbic acid content – in the fruits of plum variety Uhorka Italiis'ka and phenolic substances – in the fruits of plum variety Stanley. The latter had the highest antioxidant status. The average mass loss during storage of plum fruits was about 7.7 % or 0.23 % a day. The calculated rate constants showed that the fruits of plum variety Uhorka Italiis'ka had the maximum mass loss rate. Among the constituents of the chemical composition of plum fruits, dry matter content has a dominant influence on the daily mass loss. The regression model for mass loss prediction depending on the dry matter content has the form: y=0,018x2–0,759x+7,715. Among the weather factors, the most significant is the sum of active temperatures in the last month of the fruit formation. The equation у=1,874262–0,00211х should be used as a regression model for predicting the mass loss caused by abiotic factors.